2011
DOI: 10.1590/s1516-31802011000600005
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic characterization of acute leukemia at a public oncology reference center in Maranhão, northeastern Brazil

Abstract: CONTEXT AND OBJECTIVES: The incidence of acute leukemia (AL) subtypes varies according to geographical distribution. The aim here was to determine the incidence of morphological and immunophenotypic AL subtypes in the state of Maranhão, Brazil, and to correlate the expression of aberrant phenotypes in children with acute lymphoblastic leukemia (ALL) with prognostic factors. DESIGN AND SETTING: Single prospective cohort study at a public oncology reference center in Maranhão. METHODS: Seventy AL cases were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
7
11
0
2
Order By: Relevance
“…Moreover, the rate for common B cell ALL observed 51.6% in several studies. 11 Most of our ALL patients (44%) had common B cell ALL phenotype consistent with the literature. In addition, Scrappe et al showed that immunophenotypes were characterized by 6% pro-B ALL, nearly 75% common B cell ALL, and 19% pre-B cell ALL.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the rate for common B cell ALL observed 51.6% in several studies. 11 Most of our ALL patients (44%) had common B cell ALL phenotype consistent with the literature. In addition, Scrappe et al showed that immunophenotypes were characterized by 6% pro-B ALL, nearly 75% common B cell ALL, and 19% pre-B cell ALL.…”
Section: Discussionsupporting
confidence: 86%
“…Expression of aberrant phenotypes was more in case of males compared to females. This was comparable to the findings of Noronha et al 15 In the total study population average age was 40.65 years, average WBC count was about 53979/mm 3 , average platelet count was about 80114/mm 3 and average blast % was 62.65%. In present study, no statistically significant association was found between adverse prognostic factors and aberrant phenotypes.…”
Section: Discussionsupporting
confidence: 91%
“…This was highlighted by two independent studies carried out in south and north India, that showed the change in trends from T-All to B-ALL with the changing socioeconomic status of a single concerned population [5,6]. Similar changes have been observed in other developing nations [4]. We feel our data also supports the same hypothesis as although still considered a low middle income country from south Asia, the Sri Lankan population reaps the benefits of a well organized health care system that has pushed many of its health parameters in par with developed countries.…”
Section: Immunophenotypementioning
confidence: 68%
“…B-ALL was more frequent than T-ALL independent of the age group analyzed. The geographic variation of ALL is well established [1,4,5]. This difference has been linked to ethnicity and socioeconomic status.…”
Section: Immunophenotypementioning
confidence: 99%
See 1 more Smart Citation